The intersection between work and family roles and its relationship with self-esteem, guilt, and well-being in general at the intrapersonal and interpersonal level: A theoretical and methodological perspective - Messerli, Denise (Neuchâtel : Université de Neuchâtel, 2024)
This thesis examines the interplay between work and family roles. I examine both the intrapersonal and interpersonal perspectives. The first two studies focus on work-family conflict and its effects on self-conscious attitude (i.e., self-esteem) and on self-conscious emotion (i.e., work-family guilt). The third study focuses on the interpersonal perspective of work-family interaction. The fourth study is a methodological article that provides evidence for the study design in study 2. The four integrated studies also differ methodologically. For example, work-family conflict is examined at the level of everyday life and at the level of long-term effects (study 1 and 2). The third and fourth studies are meta-analyses that shed light on the topic of work-family conflict at the interpersonal level on the basis of primary studies (study 3) and also provide a deeper understanding of two analytical methods (i.e., CLPM and RI-CLPM) (study 4). The individual studies are embedded in previous research and discussed in a broader context.
PhD thesis submitted to the Faculty of Science, Institute of Work and Organizational Psychology, University of Neuchâtel Expert committee: Thesis director – Prof. Laurenz L. Meier, University of Neuchâtel, Switzerland Internal expert – Prof. Maike Debus, University of Neuchâtel, Switzerland External expert – Prof. Bettina S. Wiese, University of Aachen, Germany
Keywords: work-family conflict; work-family guilt; self-esteem; gender; contingencies of selfworth; daily diary study; longitudinal study; meta-analysis